FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION PRAMUNIAGA - ignatius soni kurniawan; husni tamrin (Universitas Lancang Kuning, 2019)
The purpose of the research is to test the effect of job satisfaction, affective commitment, and work stress on turnover intention. Samples taken were 95 respondents using the Slovin method. Data analysis method using multiple linear regression test. This study found that job satisfaction had no effect on turnover intention, affective commitment had no effect on turnover intention, and work stress has a significant positive effect on turnover intention.